Seven daughters & seven sons - Cohen, Barbara; Lovejoy, Bahija Fattuhi (New York : Beech Tree Books, 1994)
A retelling of a traditional Arabic tale in which a young woman disguises herself as a man and opens up a shop in a distant city in order to help her impoverished family.
Keywords: Arabs -- Folklore; Folklore -- Arab countries